Electronic government: state, citizenship and democracy on the internet? (2010)
This article deals with the proliferation of electronic governments worldwide. The theoretic perspectives profiling them are gathered here and the implementation of on-line government in Colombia is discussed to generate a consideration on the behavior of the state and society in their encounter with the world of information-technology and the so called digital era. In the first part, the article inquires about the phenomenon of electronic governments, exploring on the origins of the concept, international trends that have encouraged it, and configuring features. In a second part, the implementation of electronic government in Colombia is described. Its stages, technological components, architecture and some indicators generated by the 2009 platform are analyzed. In the third part there is a consideration on the perspectives for democracy, which underlie in the consolidation of this alliance between the state and the information technology.